2022
DOI: 10.1101/2022.03.15.484448
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pulmonary lesions following inoculation with the SARS-CoV-2 Omicron BA.1 (B.1.1.529) variant in Syrian golden hamsters

Abstract: The Omicron BA.1 (B.1.1.529) SARS-CoV-2 variant is characterized by a high number of mutations in the viral genome, associated with immune-escape and increased viral spread. It remains unclear whether milder COVID-19 disease progression observed after infection with Omicron BA.1 in humans is due to reduced pathogenicity of the virus or due to pre-existing immunity from vaccination or previous infection. Here, we inoculated hamsters with Omicron BA.1 to evaluate pathogenicity and kinetics of viral shedding, com… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Within the affected olfactory epithelium and lamina propria predominantly neutrophilic infiltrates were present, whereas the associated turbinates’ lumina contained substantial mucopurulent exudates. As reported by Rissmann et al (Rissmann et al, 2022), the hamsters infected with Delta showed more inflammation compared to Omicron BA.1 infected hamsters, which showed the least inflammatory lesions within the olfactory mucosa.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Within the affected olfactory epithelium and lamina propria predominantly neutrophilic infiltrates were present, whereas the associated turbinates’ lumina contained substantial mucopurulent exudates. As reported by Rissmann et al (Rissmann et al, 2022), the hamsters infected with Delta showed more inflammation compared to Omicron BA.1 infected hamsters, which showed the least inflammatory lesions within the olfactory mucosa.…”
Section: Resultssupporting
confidence: 70%
“…The hamster model has been proven useful to study the pathogenesis of respiratory disease caused by SARS-CoV-2 infection for different variants (Bryche et al, 2020; Frere et al, 2022; de Melo et al, 2021; Rissmann et al, 2022; Sia et al, 2020; Zazhytska et al, 2022). This study suggests that the neuroinvasiveness and neurovirulence of different SARS-CoV-2 variants can also be studied in the hamster model.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, VOC Beta( Ravi et al, 2021 ) and Gamma ( Montagutelli et al, 2021 ) could establish infection in wild-type mice, but with a milder infection than in human ACE2 transgenic mice ( Tarres-Freixas et al, 2021 ). Omicron, because of its ability to infect mice ( Bentley et al, 2021 , Liu et al, 2022 , Rissmann et al, 2022 , Suryawanshi et al, 2022 ), was hypothesized to emerge from partially fit jump species( Wei et al, 2021 ), and reversions after widespread circulation in humans could support such hypothesis. The F486V mutation found in BA.4/5 facilitates escape from certain Class 1 and Class 2 antibodies to the RBD but compromises the Spike affinity for the cellular receptor ACE2, but the R493Q reversion mutation restores receptor affinity, and consequently, the fitness of BA.4/5 ( Wang et al, 2022a ).…”
Section: Co-infections and Recombinantsmentioning
confidence: 99%